Respostas
respondido por:
3
4m-6m=-4+12-3+9
-2m=14 (-1)
2m=-14
m=-14/2
m=-7
-2m=14 (-1)
2m=-14
m=-14/2
m=-7
respondido por:
2
3 + 4m - 9 = 6m - 4 + 12
Coloque as incógnitas no mesmo lado e os numeros no outro:
4m - 6m = -4 + 12 + 9 - 3
-2m = -7 + 21
-2m = 14 *(-1)
2m = -14
m = -7
Coloque as incógnitas no mesmo lado e os numeros no outro:
4m - 6m = -4 + 12 + 9 - 3
-2m = -7 + 21
-2m = 14 *(-1)
2m = -14
m = -7
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás